“Estudio comparativo entre las garantías hipotecarias y prendarias, en la legislación civil Ecuatoriana.” - Chávez Guamán, Richar David (2017)
Within the research work entitled "COMPARATIVE STUDY BETWEEN MORTGAGE AND PREMIUM GUARANTEES, IN ECUADORIAN CIVIL LEGISLATION." We have tried to know in depth the real guarantees of mortgage and pledge, for which we investigated the mortgage, which basically it is the constitution of guarantee on a real estate. As well as, the pledge that is the constitution in guarantee of a movable good was studied. The mortgage has multiple characteristics that are its own, from the moment of its constitution, the same that is done by a public deed, because it is a real right over a property, in addition it must be registered in the Property Registry of the canton in which is found. The pledge, for its part, is constituted by a private contract with signature recognition before a Notary, which must be registered in the Mercantile Registry, the pledge may be ordinary, special trade and agricultural, depending on the movable property in question. The differentiation between the two real guarantees focuses on the object that are movable and immovable, however, there are other differences that were studied, such as the way in which the property should be seized, since the mortgage only requires the inscription of providence of the Judge, while the pledge requires judicial deposit, to avoid concealment.